DAMPAK TRAGEDI BOM DI LEGIAN KUTA TERHADAP PERAN SEKTOR PARIWISATA DALAM PRODUK DOMESTIK REGIONAL BRUTO (PDRB) BALI - I Nyoman Erawan (Journal of Indonesian Economy and Business (JIEB), 2003)
This paper aim to measure the negative impact of The Bombing Tragedy for the role of the tourism sector in Bali’s Gross Domestic Regional Product (GDRP), and to study the impact for the various sub sectors which support tourism in Bali. As tourism is the key sector for the economic development of Bali, the tragic event of The Legian Kuta Bombing is considered to have a strong negative impact for the economy of Bali.The use of the Input-Output Analysis confirmed that the bombing tragedy had reduced the role of tourism in GDRP of Bali from 59.95 percent in the year 2000 to just 47.42 percent in 2002. Economic sectors which strongly received the negative impact are: Trade sector, Hotels and Restaurants, Transportation and Communication, Manufacturing, and Agriculture, Animal Husbandry, Forestry, and Fishery.Consequently, it is the responsibility of The Local Government of Bali, together with the Central Government of Indonesia, to revive the image of Indonesia and Bali particularly as a save destination for the tourist.In the intermediate and longer term, the sectoral development strategies of Bali have to be redefined to accomodate the rapid changes that occur, which suggest the implementation of the study of Sustainable Community Tourism Development in Bali.Keywords: Tourism, Tourism Income Multiplier Effect, Input-Output Analysis, GDRP, SCTD.